The Quantification of Structural Reforms in OECD Countries: A New Framework - Balazs Egert; Peter Gal (Center for Economic Studies and ifo Institute (CESifo), 2017)
This document describes and discusses a new supply side framework that quantifies the impact of structural reforms on per capita income in OECD countries. It presents the overall macroeconomic impacts of reforms by aggregating over the effects on physical capital, employment and productivity through a production function. On the basis of reforms defined as observed changes in policies, the paper finds that product market regulation has the largest overall single policy impact five years after the reforms. But the combined impact of all labour market policies is considerably larger than that of product market regulation. The paper also shows that policy impacts can differ at different horizons. The overall long-term effects on GDP per capita of policies transiting through capital deepening can be considerably larger than the 5- to 10-year impacts. By contrast, the long-term impact of policies coming only via the employment rate channel materialises at shorter horizon.
Keywords: D24; E17; E22; E24; J08; 330; structural reforms; product markets; labour markets; regulation; simulation; multi-factor productivity; investment; employment; per capita impact; OECD